The impact of Malaysian unit trust family membership on investors' risk and returns / Teoh Teng Tenk - Teoh, Teng Tenk (2012)
This study examines the effect of unit trust investments within a fund family as opposed to across fund families in relation to the risk and return to the investors in Malaysia. The sample consists of 222 funds in 15 fund families. The study period is between 2003 and 2009. This study focuses on three aspects of risk and return of unit trust investment in relation to investing within a fund family or across families. The first part analyses the diversification benefits in terms of return correlation and its causes. This study finds evidence of unit trust returns being more closely related within fund families than outside the fund families. For this reason, investing in funds managed by the same unit trust family may not lead to a reduction of portfolio risk. It is also found that combining Islamic and conventional funds could bring additional risk reduction benefits. The money market funds stand out as a good diversification to other funds. The second aspect studied is the persistence in fund performance. This is done by examining the hot-hand phenomenon at unit trust fund family level, rather than at the individual fund level. The study finds evidence of short-term (monthly and quarterly) positive performance persistence, or the hot-hand phenomenon. However, the persistence disappears when a longer rolling period of six months and one year are considered. The hot-hand effect is generally associated with the relative superior performance in that industry as a whole. However, this study found weak evidence of hot-hand fund families, provide high excess returns to investors. Finally, this study examines the spillover effects, that is, the extent to which investors’ capital is affected by the existence of a star fund in its family. Surprisingly, the evidence suggests that investors are not responsive to the star performing identity of funds in the same family. The finding suggests that a strategy of star-creation may not be a viable approach to attract market share in this industry in Malaysia. Possible reasons underlying the results are explored and these include families’ past performance, size of the fund family and that the number of funds in the family.